2020
DOI: 10.1371/journal.pone.0230995
|View full text |Cite
|
Sign up to set email alerts
|

Higher thresholds for the utilization of steatotic allografts in liver transplantation: Analysis from a U.S. national database

Abstract: Background Historically, liver allografts with >30% macrosteatosis (MaS) on donor biopsy have been associated with early allograft dysfunction and worse graft survival; however, successful outcomes have been reported in small cohorts. This study proposes an elevated MaS threshold for organ utilization without detriment to graft survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
0
14
0
2
Order By: Relevance
“…With a rising number of new registrants in transplant waitlists, the disparity between allograft availability and waiting candidates remains persistent. To bridge this gap, there has been increasing support for the use of steatotic livers 7,43 . However, accumulating evidences showed that using steatotic grafts for LT is associated with higher risks of complications after LT 44 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With a rising number of new registrants in transplant waitlists, the disparity between allograft availability and waiting candidates remains persistent. To bridge this gap, there has been increasing support for the use of steatotic livers 7,43 . However, accumulating evidences showed that using steatotic grafts for LT is associated with higher risks of complications after LT 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Steatotic liver is a common type of ECD. However, such organs are more prone to preservation injury and graft dysfunction, resulting in a poor prognosis after liver transplantation 6‐8 . It has been proposed that steatotic livers are more susceptible to ischaemia‐reperfusion (I/R) injury, which impairs liver regeneration and is a major cause of liver damage 6,9 .…”
Section: Introductionmentioning
confidence: 99%
“… 8 Separately, our group showed equivalent 1-y graft survival for liver allografts with up to 50% MaS when used in recipients with model for end-stage liver disease (MELD) scores <33 and up to 40% MaS in higher MELD recipients. 9 Together, these findings support the use of increasingly steatotic allografts with attention to recipient selection.…”
mentioning
confidence: 66%
“…Similarly, Briceño et al were able to show in a clinical study that steatosis over 30% had an influence on IRI development; moreover, steatosis over 30% was the main cause of severe IRI in that study [ 19 ]. In addition, grafts with severe fatty degeneration more often lead to primary non-function [ 26 , 27 ]. Importantly, we found in our study that patients with a marginal transplant who developed an IRI have substantially poorer outcomes, including early mortality.…”
Section: Discussionmentioning
confidence: 99%